The physiological association between forced vital capacity and reaction time in healthy medical students - Dagradi, Eric Mayo; Kusnanik, Nining Widyah; Wahjuni, Endang Sri; Kumala, Asami Rietta; Rahayu, Indri Ngesti (Edelweiss Applied Science and Technology, 2025)
Forced vital capacity (FVC) has been proposed as a physiological factor influencing cognitive performance, including reaction time (RT). However, evidence in healthy young adults is limited. This study investigated the association between FVC and RT among medical students. A cross-sectional study was conducted with 34 healthy, non-smoking students at the Medical Students of Hang Tuah University. FVC was measured using a digital spirometer, while simple reaction time (SRT) was assessed with computerized tests. Shapiro–Wilk and Spearman’s correlation were applied for analysis. Males showed slightly higher mean FVC (93.95 ± 9.96%) compared to females (92.43 ± 7.60%). Mean SRT was nearly identical (males: 297.83 ± 61.59 ms; females: 298.78 ± 62.73 ms), while CRT was marginally faster in males (437.66 ± 101.12 ms) than in females (445.66 ± 82.39 ms). No significant correlations were found between FVC and SRT (ρ = 0.138, p = 0.437) or between FVC and CRT (ρ = 0.292, p = 0.094). In healthy young adults, FVC is not significantly associated with reaction time. Other factors such as physical fitness, neuromuscular coordination, and stress may play a stronger role. Further longitudinal research is needed to clarify the physiological links between lung function and cognitive performance.